Application of EUS or MRCP prior to ERCP in patients with suspected choledocholithiasis in clinical practice - de Jong, Mike J.P.; Engels, Megan M.L.; Sperna Weiland, Christa; Krol, Robin; Bisseling, Tanya M.; van Geenen, Erwin-Jan M.; Siersema, Peter; van Delft, Foke; van Hooft, Jeanin E. (Endoscopy International Open, 2025)
Background and study aims Patients with symptomatic cholelithiasis can be stratified according to the 2019 European Society for Gastrointestinal Endoscopy (ESGE) guideline into low-, intermediate- and high-likelihood groups for presence of choledocholithiasis. For the intermediate group, endoscopic ultrasound (EUS) or magnetic resonance cholangiopancreatography (MRCP) is recommended to assess whether an endoscopic retrograde cholangiopancreatography (ERCP) is necessary prior to cholecystectomy. The aim of the study was to investigate adherence to the guideline for diagnostic and treatment strategy for cholelithiasis in daily clinical practice.Patients and methods A multicenter, retrospective cross-sectional observational study of the diagnostic pathway of patients with suspicion of choledocholithiasis was conducted between 2019 and 2021. Patients were stratified according to the ESGE guideline "Endoscopic management of common bile duct stones”.Results A total of 305 patients were included in the analysis and stratified into low- (17%), intermediate- (40%) and high- (43%) likelihood of choledocholithiasis. In these three categories, 182 patients (60%) underwent ERCP. Adherence to the ESGE guideline recommendation was 59.7% overall and was the highest in the intermediate-likelihood group (83.6%), compared with 45.1% in the low- and 43.2% in the high-likelihood group, respectively (P < 0.001). In the high-likelihood group, 49% underwent additional imaging. In 195 patients who underwent additional imaging, 55 ERCPs (28.2%) could be avoided.Conclusions This study shows that stratification according to the ESGE guideline is useful to reduce the number of unnecessary additional imaging procedures and ERCPs in patients with a suspicion of choledocholithiasis. It seems worthwhile to perform EUS prior to ERCP in the same session.
Keywords: Pancreatobiliary (ERCP/PTCD); Stones; Endoscopic ultrasonography; Biliary tract; Quality and logistical aspects; Performance and complications; ERC topics